1994
DOI: 10.1177/0146167294204005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Free Responses and Cluster Analysis to Determine Stereotypes of Eight Groups

Abstract: A two-part study contrasted the utility of free-response and checklist methodologies for ascertaining ethnic and gender stereotypes. Descriptions of data collection, organization, and cluster and entropy analyses are provided. Results indicate that important differences emerge between data resulting from free-response methodology and those obtained with traditionally employed adjective checklists. These differences include the generation of a large percentage of physical descriptors and within-ethnic-group gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
213
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(233 citation statements)
references
References 21 publications
8
213
2
Order By: Relevance
“…However regarding attitudes by others about Asian-Ameri can men, Niemann, Jennings, Rozelle, Baxter and Sullivan (1994) found that among Uni versity of Houston students, Asian-American men were considered intelligent, short, achievement oriented, soft spoken, and hard workers. From an augmentative social repre sentation perspective, this suggests that Asian-American masculinity is socially con structed around "model minority" maleness and not in terms of the dominant construc tion of masculinity.…”
Section: About Asian-american Male Masculinitiesmentioning
confidence: 97%
“…However regarding attitudes by others about Asian-Ameri can men, Niemann, Jennings, Rozelle, Baxter and Sullivan (1994) found that among Uni versity of Houston students, Asian-American men were considered intelligent, short, achievement oriented, soft spoken, and hard workers. From an augmentative social repre sentation perspective, this suggests that Asian-American masculinity is socially con structed around "model minority" maleness and not in terms of the dominant construc tion of masculinity.…”
Section: About Asian-american Male Masculinitiesmentioning
confidence: 97%
“…The data thus obtained allow the researcher to detect stereotypes that are most strongly associated withand that are the most salient about-the objects under study (Ehrlich & Rinehart, 1965;Niemann et al, 1994;Spencer-Rodgers, 2001). Free-response technique has several shortcomings as well.…”
Section: Stereotype Measurement Techniques: Check-list Vs Free-responsementioning
confidence: 99%
“…Structured approaches prevail in social psychology research where investigators use a research instrument that contains a set of personal traits or characteristics attached to a group of people (Katz and Braly 1935;Niemann et al 1994). There are many advantages to using structured approaches: it is relatively easy to analyse the data, the findings tend to yield a well-defined structure and it is possible to make comparisons among the findings of various studies that employed the same instrument.…”
Section: Exploring Stereotype Content: Structured and Unstructured Apmentioning
confidence: 99%